“Today I Can Look in the Mirror and Like Myself”: Effects of a Trauma-Informed Mindful Recovery Program on Self-Compassion - Moore, Sarah K.; Okst, Kayley; Smith, Lydia; Fatkin, Thomas; Creedon, Timothy; Fredericksen, A. Kiera; Gawande, Richa; Schuman-Olivier, Zev (Frontiers in Psychology, 2022)
Background Opioid-related deaths continue to rise. Psychological trauma is commonly comorbid with Opioid Use Disorder (OUD). Adverse childhood experiences can disrupt the development of emotion regulation, increasing risk of substance use. Self-compassion may reduce OUD risk and outcomes by facilitating emotion regulation, decreasing the toxicity of shame, and reducing internalized stigma that can hinder recovery. Mindfulness practice enhances self-compassion. Methods This study is part of a pilot (N = 18) of the Mindful Recovery OUD Care Continuum (M-ROCC) during buprenorphine office-based opioid treatment (OBOT). The present study was conducted to gain a deeper understanding of the intervention’s effects on self-compassion development, and to explore differential changes in self-compassion during the intervention among participants with varying intensity of trauma exposure measured by high levels of childhood adversity (defined by 4+ adverse childhood experiences (ACEs) at baseline). We conducted secondary analyses of a subset of qualitative interview data (N = 11 unique participants) collected for the pilot study (weeks 4 and 24, 14 total interviews) to elaborate upon changes in Self-Compassion Scale (SCS-SF) scores. Results In the primary pilot study, participants’ mean SCS-SF scores shifted significantly from baseline to week 24, β = 0.22, p = 0.028. This change is elaborated upon through interviews. Despite pervasive challenges to becoming more self-compassionate (e.g., trauma histories and substance use), participants reported increased compassionate self-responding and decreased uncompassionate self-responding. Mindfulness training was identified as the primary mechanism underlying the shift. Kindness to self and others and—to a lesser extent an increased sense of common humanity—were also identified as key to overall self-compassion. Compared to those in the lower ACEs group, participants in the higher ACEs group tended to have lower baseline self-compassion scores (d = 1.09, p = 0.055). Conclusion M-ROCC may increase self-compassion among patients with OUD during OBOT by increasing compassionate, and decreasing uncompassionate, self-responding. Patients with OUD with greater childhood adversity tended to have lower levels of self-compassion, which improved with M-ROCC. Future trials with larger samples are needed to confirm these potential outcomes, mechanisms, and differential impacts between ACEs subgroups.